A cross-sectional study to assess medical student’s opinions regarding child sexual abuse in an Eastern state of India - Rastogi, Ashok Kumar; Debbarma, Shibajee (International Journal Of Community Medicine And Public Health, 2024)
Background: Child sexual abuse (CSA) is a heinous crime against growing children, which may victimize both genders. It is a pervasive issue that affects societies worldwide. Present study was conducted to gain insights into the opinion and understanding regarding CSA among undergraduate medical students at a premier institution in Bihar, an Eastern state of India. Objectives were to study the distribution of medical students according to opinions regarding CSA and to study the distribution of medical students according to information regarding CSA obtained from parents. Methods: After obtaining institutional ethical committee (IEC) clearance, a pre-designed structured questionnaire was administered online to undergraduate medical students of the institution who gave consent for study. Collected information was entered in Microsoft excel, and categorical variables were expressed as percentages and proportions. Results: The present study included 312 boys (62.4%) and 186 girls (37.6%). The majority (82.2%) of study participants agreed that boys are also victims of CSA, and the majority (68.3%) agreed with the statement regarding informing a caregiver following an incident. Most (64%) of the study participants had obtained information regarding CSA from parents. Conclusions: Awareness generation is an important measure to curb the growing menace of CSA. Parental education plays a vital role in creating necessary awareness.